Analysis of Judicial Activism and its Impact on Parliamentary Democracy in Pakistan; Case Study of 2018-2022 - Wareesha Khan; Sher Hassan (Review Journal of Social Psychology & Social Works, 2025)
This research study explores the concept of judicial activism and conducts analysis of the judicial activism taking by the judiciary of Pakistan, during 2018-2022. Judicial activism refers to the proactive role of the judiciary in addressing societal issues and promoting social justice, often with Suo moto notices, where the court takes cognizance of a matter on its initiative. The analysis has focused on the judicial activism and its impact on Parliamentary system of Pakistan. This research study has examined the key areas of intervention, such as parliamentary sovereignty, legislative inertia and political tension, disrupted power dynamics, policy making. This study has utilized qualitative research methodology, including an interview and comprehensive review of relevant literature. This research study found that excessive judicial activism has badly affected parliamentary democracy of the country. This research study recommends that the judiciary should play a balancing role and do not interfere with the legislative authority to have an effective parliamentary democratic system in the country.